Impact of Nanoparticle Addition and Ozone Pre-Treatment on Mesophilic Methanogenesis in Temperature-Phased Anaerobic Digestion - Encarnación Díaz Domínguez; María Eugenia Ibañez López; Jacek Mąkinia; Francisco Jesús Fernández-Morales; José Luis García Morales (Applied Sciences)
Biodegradable organic waste offers significant opportunities for resource recovery within the frame of the circular economy. In this work, the effects of carbon-encapsulated iron nanoparticles and ozone pre-treatments in the mesophilic methanogenic stage of a temperature-phased an-aerobic digestion have been studied using biochemical methanogenic potential (BMP) tests and modeling simulation. To do that, digestates from a pre-treated thermophilic acidogenic reactor that co-digested sludge and wine vinasse were used. The addition of nanoparticles favored the removal of particulate matter, which increased by 9% and 6% in terms of total solids and volatile solids, respectively. When combined with ozone pre-treatment, these increases were 27% and 24%, respectively, demonstrating enhanced AD efficiency. The dose of iron nanoparticles encapsulated in carbon did not result in a statistically significant increase in methane production when sludge and vinasse were used as feedstock. The combination of nanoparticles with the ozone pre-treatment significantly improved the methanogenic phase of the second stage, increasing the methane production yield by 22% and reducing the lag phase from 10 days to 3 days, according to the modified Gompertz model.